2022
DOI: 10.3389/fgene.2022.907392
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Necroptosis-Associated IncRNAs Signature for Prognosis of Head and Neck Squamous Cell Carcinoma

Abstract: Purpose: The prognosis of head and neck squamous cell carcinoma (HNSCC) is poor. Necroptosis is a novel programmed form of necrotic cell death. The prognostic value of necroptosis-associated lncRNAs expression in HNSCC has not been explored.Methods: We downloaded mRNA expression data of HNSCC patients from TCGA databases. Prognostic lncRNAs were identified by univariate Cox regression. LASSO was used to establish a model with necroptosis-related lncRNAs. Kaplan-Meier analysis and ROC were applied to verify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Although long noncoding RNAs (lncRNAs) cannot directly encode proteins, they can regulate gene expression by altering how genes are translated or by directly interacting with proteins and other RNA species. 19,20 They may be essential for the regulation of anticancer immune responses, including antigen release, antigen presentation, immune activation, immune cell migration, immune cell infiltration, and cancer cell death, according to accumulating evidence. 21,22 For instance, a research revealed that Linc00176 might release miRNAs (such miR-9 and miR-185) to downregulate target mRNAs, therefore mediating hepatocellular carcinoma cell necrosis and inhibiting the growth of hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although long noncoding RNAs (lncRNAs) cannot directly encode proteins, they can regulate gene expression by altering how genes are translated or by directly interacting with proteins and other RNA species. 19,20 They may be essential for the regulation of anticancer immune responses, including antigen release, antigen presentation, immune activation, immune cell migration, immune cell infiltration, and cancer cell death, according to accumulating evidence. 21,22 For instance, a research revealed that Linc00176 might release miRNAs (such miR-9 and miR-185) to downregulate target mRNAs, therefore mediating hepatocellular carcinoma cell necrosis and inhibiting the growth of hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Although long noncoding RNAs (lncRNAs) cannot directly encode proteins, they can regulate gene expression by altering how genes are translated or by directly interacting with proteins and other RNA species 19,20 . They may be essential for the regulation of anticancer immune responses, including antigen release, antigen presentation, immune activation, immune cell migration, immune cell infiltration, and cancer cell death, according to accumulating evidence 21,22 .…”
Section: Introductionmentioning
confidence: 99%